Peran Pemerintah Dalam Pemberdayaan Petani Kentang di Kabupatenn Banjarnegara - Angga Fredika; Rina Martini; Nunik Retno Herawati (Journal of Politic and Government Studies, 2014)
AbstracThe decrease of potatoes harvest in Banjarnegara Regency was caused by several problem. Such as farmers excessive habit in farm opening, over-control pesticide sprayed, lack of quality seeds, and conventional farming methods. Because of that, Government aid is very needed to make an empowerment.This study was held with quantitaative methods. Using descriptive approach the data was collected by literature studies and interview with associated informants. Such as Head of Agricultural Department, Agricultural conselling bodies, Farmers society, and the farmers whose undergo the problems.The result of this study shown that government rules wich is presented by agriculture, fishery, and ranch services of Banjaregara Regency was not succeeded yet. The data was reflect status quo of Banjarnegara farmings that still very less-quality seeds, lot of farmers were not familiar with advance farming technology, rarely farming counselling from government, unavailable saving and loan bodies, and the environmental damage by farmer excessive eploitations.To solve that problem government need to make several actions : facilitating more farmers group to make an self quality seeds wich approprite with farming standart, to make annual induction government need more instructors, educate rights pesticide usage, establish save and loan department to back up farmers capital to developing its business, and require annual environment conservation to avoid nature damage.Keyword : Government role, Empowering, Potatoes Farmer